Repetition in the Letters of the Umayyad Era in the Book of Jamharat Rassael Al Arab in the Modern Arab Ages of Ahmed Zaki Safwat - Alawi, Mohammed Mahmood; Mohammed, Saja Jassim (Al-Adab Journal, 2020)
Prose, in general, and the art of writing letters, in particular, have been developed by the Holy Quran and the Islamic religion. The learning of writing and reading and the transformation from speaking into writing have also been improved similarly. As such, prose has become equal to poetry or even better. So, writing has been a profession and a part of the state affairs. The caliphs themselves started addressing princes, ministers, army leaders, and likewise. Therefore the letters played a vital role at that time. It is a written text from the sender to the receiver about a certain topic. These letters have been characterized by eloquence and dexterity and by cohesion and coherence.This study has been chosen because it has never been done before.